Genetic studies on 305 days and test day milk yield records in Murrah buffaloes - CHAKRABORTY, D; DHAKA, S S; PANDER, B L; YADAV, A S; DANDAPAT, A (The Indian Journal of Animal Sciences, 2010)
Data pertaining to first lactation records on 326 Murrah buffaloes, progeny of 48 bulls calved during 1987 to 2006, maintained at Buffalo Research Centre, Chaudhary Charan Singh Haryana Agricultural University, Hisar, were analyzed. The overall population means were 1 818.06 kg, 4.43 kg, 7.90 kg, 8.11 kg, 7.82 kg, 7.81 kg, 7.25 kg, 6.64 kg, 6.07 kg, 5.37 kg and 5.13 kg for 305 days milk yield and first 10 test day records TD1, TD2, TD3, TD4, TD5, TD6, TD7, TD8, TD9 and TD10, respectively. Period of calving had significant effect on TD1, TD7 and TD9. However, season of calving had nonsignificant effect on all the traits under this study except for 305 days milk yield. The estimates of heritability of various traits were not significantly different from zero as standard errors of estimates were higher. The genetic correlations for all traits were moderate to high except for TD2 with TD7 and TD9, where low estimates were obtained. The phenotypic correlations were moderate to high and in some cases negative.